2001
DOI: 10.1139/w01-097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacteria isolated from rice for plant growth promotion and biological control of seedling disease of rice

Abstract: Of 102 rhizoplane and endophytic bacteria isolated from rice roots and stems in California, 37% significantly (P < or = 0.05) inhibited the growth in vitro of two pathogens, Achlya klebsiana and Pythium spinosum, causing seedling disease of rice. Four endophytic strains were highly effective against seedling disease in growth pouch assays, and these were identified as Pseudomonas fluorescens (S3), Pseudomonas tolaasii (S20), Pseudomonas veronii (S21), and Sphingomonas trueperi (S12) by sequencing of amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 20 publications
2
42
0
1
Order By: Relevance
“…Likewise, studies report on Sphingomonas spp. as producers of plant growth-stimulating factors (2,10,46).Another way in which plants could benefit from their commensal bacteria is by protection against invading pathogens. In the past, several efforts to find natural agents for the control of foliar plant pathogens have been made (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies report on Sphingomonas spp. as producers of plant growth-stimulating factors (2,10,46).Another way in which plants could benefit from their commensal bacteria is by protection against invading pathogens. In the past, several efforts to find natural agents for the control of foliar plant pathogens have been made (20).…”
mentioning
confidence: 99%
“…Likewise, studies report on Sphingomonas spp. as producers of plant growth-stimulating factors (2,10,46).…”
mentioning
confidence: 99%
“…1,16) Taken together, certain contributions of the rhizospheous sphingomonads to rice production were tentatively inferred. 16,37) In fact, in ammonia-assimilating Melastoma malabathricum, it has been found that S. rosa EC-K013 promotes the growth of saplings under nitrogen-starving and strongly acidic (pH 3.0) nursery conditions. 38) Our sphingomonad-detecting DNA array probes made it possible to investigate and pursue microfloral succession in the rhizosphere of several acid-tolerant plants, since the rhizospherous sphingomonads are most likely to be a mediator in the rhizosphere of acid-tolerant plants in South and Central Kalimantan.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely a reason why Sphingomonas spp. are often found as plant-associating bacteria, particularly on the surfaces of roots (24), leaves (10), flowers (10), and seeds (10,17), and even in inner tissues as endophytes (1,5). Another unique property of Sphingomonas spp.…”
Section: Discussionmentioning
confidence: 99%